Teds-easy - descrição automática de transducer electronic data sheet - Garcia, Welington Luis Codinhoto [UNESP] (2014)
This work presents a tool for automatic description of TEDS (Transducer Electronic Data Sheet), facilitating the configuration of transducers on a network of smart sensors according to the IEEE 1451 standard.'s TEDS are virtual tables defined in the IEEE 1451 standard containing the description of the transducers. In developing this tool called TEDS-EASY used the language of web programming JSP (Java Server Pages) and database system PostgreSQL database. We also used the UML (Unified Modeling Language) to perform the modeling project. Tests with TEDS-EASY system were performed in order to validate the TEDS generated through manual descriptions and descriptions found in the literature, comparing with the description obtained when using the tool for describing TEDS show in this project